2014
DOI: 10.1007/s00125-014-3370-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prediction model for fatal and non-fatal coronary heart disease and cardiovascular disease in patients with newly diagnosed type 2 diabetes mellitus: The Basque Country Prospective Complications and Mortality Study risk engine (BASCORE)

Abstract: This study is the first southern European validated population-derived model for predicting 5-year fatal/non-fatal CHD and CVD risk in patients with newly diagnosed type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…In the ERICE study, total cholesterol did not show a statistical association with cardiovascular events, however it was not sufficiently powered to assess the impact of HDL-C. Recent data from a study carried out in patients recently diagnosed with diabetes mellitus [ 16 ], identified the ratio of non-HDL-C to HDL-C as a significant predictor of cardiovascular events, while LDL-C and TC did not show significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…In the ERICE study, total cholesterol did not show a statistical association with cardiovascular events, however it was not sufficiently powered to assess the impact of HDL-C. Recent data from a study carried out in patients recently diagnosed with diabetes mellitus [ 16 ], identified the ratio of non-HDL-C to HDL-C as a significant predictor of cardiovascular events, while LDL-C and TC did not show significant associations.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies have indicated an inverse association between HDL cholesterol and the risk of CVD among patients with type 2 diabetes. [8][9][10] However, only one Japanese study has found an inverse association of HDL cholesterol with total stroke risk among patients with type 2 diabetes in the last 10 years. 18 The present study also found an inverse association between serum HDL cholesterol levels and the risk of total stroke among patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk engines have been developed for diabetes patients, targeted at predicting specific disease outcomes such as cardiovascular diseases 17 20 , stroke 21 , and end-stage renal disease 22 . However, few studies have been conducted to assess overall mortality risk for diabetes patients.…”
Section: Discussionmentioning
confidence: 99%